Priority 3: Socio-economic dynamics and global markets - Callieris R.; Adinolfi F.; Capitanio F.; Santeramo F.G. (Feeding knowledge, 2017)
By a brief introduction of the main conceptual aspects of food security, this work point out the shift from a former focus on food energy availability to a more comprehensive appraisal of this phenomenon in recent times in the South Mediterranean countries. The most likely causes of recent rises in food prices are also described. Food security issues are analyzed in connection with rural poverty issues and with the failure to achieve successful agricultural development in some developing countries, which sometimes have to overcome strong restrictions concerning the availability of land and water resources for food production. The paper points to the convenience of using multivariate statistical tools to summarize a wealth of food security-related indicators, and a practical example of the use of Principal Components Analysis (PCA) for data concerning SEMC countries is provided, with a dataset originally comprising 11 variables. The PCA methodology is described in a non-mathematical fashion, also showing the basic steps in its application to this case. Two basic composite indicators, or ‘principal components’ are selected, one in connection with ‘human development’ and the other with ‘being at risk of hunger’, and countries in the sample are ranked according to their situation with regards to these dimensions.
Expo Milano 2015